2009
DOI: 10.3346/jkms.2009.24.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Complementary and Alternative Medicine in a General Population in South Korea: Results from a National Survey in 2006

Abstract: The purpose of this survey was to obtain information on the prevalence, costs, and patterns of use of complementary and alternative medicine (CAM) in a general population in the Republic of Korea. In 2006, we conducted nationwide and population-weighted personal interviews with 6,021 adults ranging from 30 to 69 yr of age; the final sample consisted of 3,000 people with a 49.8% response rate. In addition to their general socio-demographics, the respondents were asked about their use of CAM during the previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
83
3
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 14 publications
11
83
3
9
Order By: Relevance
“…However, many studies have found that the reliability of self-reported histories of cancer screening show good agreement with medical records (Caplan et al, 2003;Hoffmeister et al, 2007;Jones et al, 2008). In addition, the response rate in our study was 46.6%; however, compared to other nationwide studies conducted in Korea, in which the response rates were less than 50% (Ock et al, 2009;Park et al, 2011), our response rate can be considered to be acceptable. Despite some limitations, this study used data from a large nationwide, populationbased survey.…”
Section: Discussioncontrasting
confidence: 49%
“…However, many studies have found that the reliability of self-reported histories of cancer screening show good agreement with medical records (Caplan et al, 2003;Hoffmeister et al, 2007;Jones et al, 2008). In addition, the response rate in our study was 46.6%; however, compared to other nationwide studies conducted in Korea, in which the response rates were less than 50% (Ock et al, 2009;Park et al, 2011), our response rate can be considered to be acceptable. Despite some limitations, this study used data from a large nationwide, populationbased survey.…”
Section: Discussioncontrasting
confidence: 49%
“…(17.8%), others (traditional market) (14.7%), oriental medicine healthcare workers (13.5%) and friends (11%); similar results have been reported from a National Survey in 2006 in a general population in South Korea [32]. Regarding reasons for CAM use, the main cause was: "dissatisfaction toward allopathic medicine and/or treatments were not available for a specific illness" (39.8%), "traditional background, belief in the alternative system and individual philosophical viewpoint" (16.9%), "others" (in case of hearing good comments on certain alternative therapy or personal experience of positive side effects) (16.3%), and "a hope for fewer side effects" (14.4%).…”
Section: Discussionsupporting
confidence: 85%
“…However, our finding is comparable with studies conducted in Malaysia, Canada, and Korea (62.5%, 71.2%, and 74.8%, resp.) [24][25][26]. The high prevalence of CAM use in our study could be partially explained by the fact that the culture in Ethiopia encourages the use of CAM especially herbal based traditional medicine and spiritual healing.…”
Section: Discussionmentioning
confidence: 87%